Breakeven and its impact on the financial decisions of publishing companies in Lima - Fernández Bedoya, Víctor Hugo (2018)
Objective: to know if the breakeven impacts in the financial decision making of the publishing companies in Lima. Method: basic type research, sample constituted by 32 general managers of small and medium enterprises dedicated to the publishing sector in Lima, to whom they applied a survey in order to validate or reject the hypothesis formulated by the author, this being the application breakeven will have a positive impact on the financial decision-making of the publishing companies in Lima. Results: through Fisher's exact test (p.-5%), the value of 0,713 was obtained as p-value, which is greater than the value of 0,05, which is the used for the 95% confidence level, therefore, the hypothesis proposed by the researcher is accepted. Conclusions: there is a relationship between breakeven and decision making, which positively influences the financial decision making of the publishing companies in Lima; in the same way, it can be concluded that there will be better processes and solutions thanks to an adequate decision making, in the case of implantation, the calculation of the breakeven as a management tool.